PEMANFAATAN DAN PEMASARAN ROTAN DI DESA BUNTOI KECAMATAN KAHAYAN HILIR KABUPATEN PULANG PISAU - Mayawati, Sari (Lambung Mangkurat University-Indonesia, 2024)
Rattan natural resources at the research site are a source of community business in order to improve the local community's economy. The research objectives identify the form of rattan utilization, analyze the income level of the community, analyze the contribution of rattan craftsmen's business to the level of welfare, analyze the marketing process and marketing efficiency of rattan. The method used is by describing the form of rattan utilization, calculating the income of rattan craftsmen with other business income, dividing the income of rattan craftsmen to the total income of craftsmen, subtracting the selling price at the consumer level with the purchase price at the producer level, while efficient marketing divides the total cost of marketing against the total value of the product. The results showed a total of 1,044 units of finished rattan products/year consisting of bracelets, small bags, large bags, mats, serving hoods, hats, and baskets. The average income of the rattan craftsmen (respondents) is Rp. 29,726,538/year. The contribution of rattan craftsmen to the income level of the people in the research location is 38%. The total marketing margin at the intermediary producer level is Rp. 151,000 with an average marketing efficiency of 13.84